Internal and External Factors Affecting Banking Profitability: Evidence from Dual Banking System in Indonesia - Ikhsana, Nadya Ramadhani; Achsani, Noer Azam; Irfany, Mohammad Iqbal (Islamic Economics Methodology, 2025)
Implementing the dual banking system in Indonesia offers options for customers to use banking services. Before selecting which service to use, customers should perceive each bank's advantages and disadvantages. It can be carried out by conducting a performance evaluation of each bank that generates high profitability measured by the Return on Assets (ROA) value. This study aims to perform internal and external factors analysis that affect bank profitability and to compare profitability between Islamic and Conventional banking in Indonesia using the Vector Error Correction Model (VECM) method. The result shows that variable Capital Adequacy Ratio (CAR) and Financing to Deposit Ratio (FDR) have a significant positive effect on Islamic Model in the long term, whereas policy rate and oil price (COP) hold a significant negative effect. In the Conventional Model, variable CAR, policy rate, and COP hold a significant positive effect, while the exchange rate shows a negative effect. FEVD results indicate that in Islamic Model, the diversity of banking profitability can be explained by various variables, indicating that Islamic banking is more engaged in the real sector than conventional banking.